Genomic and Epidemiological Evidence of a Dominant Panton-Valentine Leucocidin-Positive Methicillin Resistant Staphylococcus aureus Lineage in Sri Lanka and Presence Among Isolates From the United Kingdom and Australia - McTavish, Sharla M.; Snow, Sarah J.; Cook, Ellie C.; Pichon, Bruno; Coleman, Sarah; Coombs, Geoffrey W.; Pang, Stanley; Arias, Cesar A.; Díaz, Lorena; Boldock, Emma; Davies, Steve; Udukala, Mangala; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Objective: To undertake the first detailed genomic analysis of methicillin-resistant Staphylococcus aureus (MRSA) isolated in Sri Lanka. Methods: A prospective observational study was performed on 94 MRSA isolates collected over a four month period from the Anuradhapura Teaching Hospital, Sri Lanka. Screening for mecA, mecC and the Panton-Valentine leucocidin (PVL) -associated lukS-PV/lukF-PV genes and molecular characterisation by spa typing was undertaken. Whole genome sequencing (WGS) and phylogenetic analysis was performed on selected multilocus sequence type (MLST) clonal complex 5 (CC5) isolates from Sri Lanka, England, Australia and Argentina. Results: All 94 MRSA harboured the mecA gene. Nineteen spa types belonging to nine MLST clonal complexes were identified. Where origin of the sample was recorded, most isolates were from skin and soft tissue infections (70/91; 76.9%), with fewer causing bacteraemia (16/91; 17.6%), empyema (3/91; 3.3%) and osteomyelitis (2/91; 2.2%). Sixty two (65.9%) isolates were PVL positive with the majority (56 isolates; 90.3%) belonging to a dominant CC5 lineage. This lineage, PVL-positive ST5-MRSA-IVc, was associated with both community and hospital-onset infections. Based on WGS, representative PVL-positive ST5-MRSA-IVc isolates from Sri Lanka, England and Australia formed a single phylogenetic clade, suggesting wide geographical circulation. Conclusions: We present the most detailed genomic analysis of MRSA isolated in Sri Lanka to date. The analysis identified a PVL-positive ST5-MRSA-IVc that is prevalent among MRSA causing clinical infections in Sri Lanka. Furthermore, this clone was also found among isolates from the United Kingdom and Australia.